Peculiarities of the study of Au-Ti-Pd-n⁺-n-n⁺-Si multilayer contact structure to avalanche transit-time diodes - Romanets, P.M.; Konakova, R.V.; Boltovets, M.S.; Basanets, V.V.; Kudryk, Ya.Ya.; Slipokurov, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
In this work, the method of electrophysical diagnostics of ohmic contacts to n⁺-n-n⁺ structures for powerful silicon impact ionization avalanche transit-time diodes has been proposed. The specific resistivity of the Au–Ti–Pd–n⁺-n-n⁺-Si contacts and the current-flow mechanism within the temperature range 100…360 K has been investigated. The generalized method for studying the temperature dependence of the specific contact resistance in the case of multilayer structures with non-uniform doping levels has been proposed. The values of the specific contact resistance have been calculated from the temperature dependence of the total resistance of the vertical structure. The offered method can be used to control the electrophysical parameters of ohmic contacts between the etching cycles in the technology of manufacturing powerful silicon impact ionization avalanche transit-time diodes.